Congenital Colonic Stenosis: A Rare Gastrointestinal Malformation in Children - Karbasian, Fereshteh; Vahedi, Zahra; Ziaee, Kiarash; Abolhassan Choubdar, Farhad (Student Research in Translational Medicine, 2023)
Congenital colonic stenosis is a condition in which there is a narrowing or blockage of the colon (large intestine) present at birth. This can occur due to multiple etiologies, including abnormal development of the colon during fetal development and some genetic defects. The condition may lead to symptoms such as abdominal pain, on and off constipation, abdominal distention and vomiting. Treatment may involve surgery to remove or widen the narrowed segment of the colon.